Environmental-friendly ballpoint and highlighter ink using pigments from chromobacterium violaceum and serrtia marcescens - Nur Nazrina Ahmad Sabri, 1989-; Wan Azlina Ahmad, supervisor; Fakulti Sains (2012)
Thesis (Sarjana Sains (Kimia)) - Universiti Teknologi Malaysia, 2012